A membrane vesicle-based assay to enable prediction of human biliary excretion. (12th February 2013) - Colombo, Federico; Poirier, Hugo; Rioux, Nathalie; Montecillo, Maria Arias; Duan, Jianmin; Ribadeneira, Maria D.
Abstract: 1. Prediction of biliary excretion is a challenge due to the lack of in vitro assays. Our laboratory previously demonstrated a highly significant correlation between in vitro IC50 values against mrp2 using rat canalicular liver plasma membrane vesicles and in vivo biliary excretion (Colombo et al ., 2012). This study explores the possibility of predicting in vivo biliary excretion in human using membrane vesicles prepared from MDCKII cells transfected with human ABCC2. 2. In vitro MRP2 activity was determined by measuring the ATP-dependent uptake of 5(6)-carboxy-2′, 7′-dichlorofluorescein (CDCF) in inside-out membrane vesicles isolated from MDCK-ABCC2 cells. CDCF uptake was time- and concentration-dependent ( K m of 4.0 ± 1.2 µM and a V max of 7.8 ± 0.9 pmol/mg/min) and inhibited by benzbromarone and MK-571 with IC50 values of 1.2 and 7.6 µM, respectively. 3. A significant linear correlation ( r 2  = 0.790) between the in vitro IC50 values from the described MRP2 assay and in vivo biliary excretion in humans was observed using 11 well-documented drugs covering low to high biliary excretions. 4. This study demonstrates, for the first time, that inhibition of CDCF uptake in MDCKII-ABCC2 vesicles not only provides a screening assay to assess MRP2 drug–drug interaction potential, but is also predictive of human MRP2-mediated biliary excretion.